Multifactorial Model and Treatment Approaches of Refractory Hypotension in a Patient Who Took an ACE Inhibitor the Day of Surgery - Karan Srivastava; Vikas Y. Sacher; Craig T. Nelson; John I. Lew (Case Reports in Anesthesiology)
In the field of anesthesiology, there is wide debate on discontinuing angiotensin-converting enzyme inhibitor (ACEI) and angiotensin receptor blocker (ARB) therapy the day of noncardiac surgery. Although there have been many studies attributing perioperative hypotension to same-day ACEI and ARB use, there are many additional variables that play a role in perioperative hypotension. Additionally, restoring blood pressure in these patients presents a unique challenge to anesthesiologists. A case report is presented in which a patient took her ACEI the day of surgery and developed refractory hypotension during surgery. The evidence of ACEI use on the day of surgery and development of hypotension is reviewed, and additional variables that contributed to this hypotensive episode are discussed. Lastly, current challenges in restoring blood pressure are presented, and a basic model on treatment approaches for refractory hypotension in the setting of perioperative ACEI use is proposed.